0341 Preliminary Effects of a Music Intervention on Actigraphy-Measured Sleep Among Older Adults with Dementia. (27th May 2020) - Mu, C; Lee, S; Risal, P G; Vigoureux, T F; Bugos, J; Meng, H
Abstract: Introduction: Music may benefit sleep and daytime alertness by decreasing stress, increasing attention, and potentially, slowing the progression of dementia. This study examined preliminary effects of a group-based music intervention on sleep health among older adults with dementia. Methods: Participants were older adults with dementia living in an assisted living facility ( n =9; M age =80.11; M range =63−89 years). Cohort 1 ( n =4) received the intervention in the morning and cohort 2 ( n =5) received the intervention in the afternoon. Participants completed a 4-week intervention protocol (12 sessions) along with a one-week actigraphy sleep assessment before and after the intervention. Informed by sleep literature, we constructed a composite sleep health score encompassing Regularity, Satisfaction or quality, Alertness, Timing, Efficiency, and Duration (higher scores indicating more daily sleep problems). Using descriptive statistics and multilevel modeling, we evaluated preliminary effects of the intervention on overall sleep health and each of the sleep dimensions. Results: Six out of nine participants exhibited a decrease in overall sleep problems at post-intervention. All 4 participants in cohort 1 showed improvement in overall sleep health at post-intervention. Specifically, in cohort 1, participants exhibited a decline in nightly sleep problems, decreased daytime nap duration, and number of naps. In contrast, while two out of five participants in cohort 2 exhibited improvement in overall sleep health, the remainder of the participants exhibited no improvement in daily sleep problems, especially in nap domains. Across cohorts, those younger in age, with vascular dementia, lower weight, and not taking sleep or hypertension related medications tended to respond better to the intervention. Conclusion: Our preliminary results demonstrate the feasibility and potential benefit of a group-based music intervention in improving overall sleep health among older patients with dementia. Implications for conducting community-based non-pharmacological interventions to improve sleep and daytime functioning among older adults with dementia will be discussed. Support: This work was supported, in part, by the Florida Department of Health Ed and Ethel Moore Alzheimer's Disease Research Award (PI: Meng, Grant #9AZ28).